Tinjauan Hukum Islam Terhadap Ritual Lewak Tapo Di Desa Weranggere Kec. Witihama Kab.Flores Timur - Jakaria M. Sali; Iskandar; Aini Aprilariesta Hanggarani; Marwan Gazali (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study is entitled "Study of Islamic Law on the Ritual of Lewak Tapo (Coconut Splitting) in Weranggere Village, Witihama District, East Flores Regency." This study aims to determine the process of implementing the lewak tapo worship and review the sharak law regarding the lewak tapo worship. The background to this study is based on a phenomenon that occurs in the Weranggere Village community, where the lewak tapo ceremony is carried out when someone dies unnaturally (misfortune). This study uses a type of field study with a qualitative approach. The results of the study show that the lewak tapo ritual is a ceremony that must be carried out if someone dies unnaturally; if it is not carried out, death in the same way will be repeated in the next generation. This ritual focuses on communicating with rera wulan tana ekan (creator of heaven and earth) and ina ama koda kewokot (ancestors) by asking for guidance from them so that during the implementation of the worship, guidance or clarity is given from the dead outside the tabii. However, in the view of sharak as explained in Q.S Yunus: 10: 106, this verse explains the prohibition on praying and worshiping other than Allah SWT. This study concludes that the lewak tapo worship is a worship that is contrary to Islamic law because the implementation process does not follow Islamic law, so it is said that this worship is an act of shirk.